Accounting Gap Analysis and the Impact of PSAK 117 on the Financial Statements of PT Asuransi Jiwa XYZ - Delfia, Elene; Wondabio, Ludovicus Sensi (E-Jurnal Akuntansi, 2025)
The purpose of this study is to analyze the implementation of PSAK 117 at PT XYZ through gap analysis, the impact of implementation on the presentation and measurement of financial statements of the opening balance on January 1, 2024, and the analysis of the financial impact on PT Asuransi Jiwa XYZ, a digital-based insurance company in Indonesia. The implementation of PSAK 117 is mandatory for all insurance companies and will be effective on January 1, 2025. The insurance contract measurement model based on PSAK 117 is the General Measurement Method or GMM measurement and with the Premium Allocation Approach (PAA) option if it meets the requirements. The problem in this research is that PT XYZ uses the PAA measurement method without a PAA feasibility test. The research method used is a qualitative single case study approach with primary and secondary data in the form of interviews and documentation. Data were analyzed using content analysis. The results of the study show that there are four gaps between the current conditions of PT XYZ and the requirements of PSAK 117, namely related to the definition of the contract, the level of aggregation, loss-making contracts and the premium allocation approach measurement method. The impact of implementing PSAK 117 for the opening balance of January 1, 2024 is a change in presentation according to the requirements, namely the derecognition of PSAK 104 and the recognition of PSAK 117. There are significant adjustments to assets and liabilities related to insurance and reinsurance contracts. Meanwhile, the impact on equity is due to the recognition of amortized acquisition cash flows over time. It is hoped that this research can provide contributions related to insight to management and stakeholders regarding the impact of insurance contract reporting, additional literature on the implementation of PSAK 117, understanding traditional insurance to digital insurance and become a reference for other insurance companies facing challenges in implementing PSAK 117. Keywords: PSAK 117; Financial Statement; Implementation; Life Insurance